Multislice computed tomography angiography is a sufficient method for detecting native aortic coarctation in children - BARIŞ, SAFA (EKIN TIBBI YAYINCILIK LTD STI-EKIN MEDICAL PUBL, 2011)
Background: We evaluated the feasibility and utility of low dose multislice computed tomography (MSCT) angiography as a noninvasive method in detecting anatomic structures of lesion and combined anomalies associated with coarctation of the aorta. Methods: A total of 15 pediatric patients (9 boys, 6 girls; mean age 34 month:3; range 8 days to 10 years) who underwent color Doppler echocardiography (CDE) and MSCT angiography for coarctation in our clinic between February 2009 and June 2010 were included in this study. The thorax was scanned from the cupula to the top of the diaphragm by using 16-slice computed tomography. Results: Upon axial imaging, anatomical findings related with coarctation were not apparent in two patients (86.6%; n=2). The three-dimensional images clearly showed all of the areas of coarctation (100%; n=15). The overall sensitivity of MSCT diagnosis for coarctation was 100%, which was higher than CDE (86.6%; n=13). The diagnosis for each patient was confirmed with surgery. Conclusion: The study proved the feasibility and efficiency of low-dose MSCT angiography as a noninvasive method to detect the native aortic coarctation in children.
Keywords: Children; coarctation of the aorta; multislice computed tomography; CONGENITAL HEART-DISEASE; MULTIDETECTOR CT; YOUNG-CHILDREN